NATIONAL DEVELOPMENT : A COMMON RELIGIOUS ISSUE FOR MEN & WOMEN IN NIGERIA - Onyema Anyanwu, Herbert (Journal of Dharma, 1988)
One of the major forces which sustained the zeal for independence was the need for development. Many nationalists believed that development would necessarily follow independence. These nationalists maintained that as soon as citizens were allowed to manage their own affairs without directives from the colonial masters, they would so conduct the nation's affairs that they would be at par with the level of development already reached by the developed countries. With this in mind, development was seen in terms of increasing the material well-being of the nation. That this was the case was amply shown in the policies and programmes of the first Republic, for as soon as independence was attained the government put forward an elaborate development plan. Since then the country has planned on five-year basis.